Vier van de infanterie : hun laatste dagen aan het Westelijk front. - Johannsen, Ernst (Zeist : Ploegsma, 1929)
Collectie Vrijzinnige Werkmansbibliotheek
Nederlands
Monografie
Keywords: Vrijzinnige Werkmansbibliotheek